Integrating Islamic Values into Local Governance through Participatory Leadership in Indonesia - Ferdi Yufriadi; Valensius Ngardi (Tanfizi : Journal of Islamic Constitutional and Political Law, 2025)
This study explores the integration of Islamic values into local governance through participatory leadership within the context of Indonesian local government. As the world’s largest Muslim-majority country, Indonesia provides a unique socio-political environment where religion and governance intersect. The research emphasizes how participatory leadership, grounded in Islamic ethical principles such as justice (‘adl), consultation (shura), and accountability (amanah), contributes to policy-making processes that are inclusive, transparent, and culturally resonant. By employing a qualitative approach with case studies in West Sumatra, this article analyzes how local leaders incorporate Islamic values into decision-making mechanisms, particularly in areas related to social welfare, community participation, and sustainable development. Findings indicate that participatory leadership practices inspired by Islamic values strengthen trust between government and society, enhance legitimacy of policies, and encourage broader civic engagement. However, challenges remain in balancing traditional Islamic values with contemporary governance demands, particularly in maintaining policy effectiveness amid political pluralism and bureaucratic constraints. The academic contribution of this study lies in advancing the theoretical linkage between participatory leadership and Islamic governance values, proposing a context-specific governance model that enriches leadership studies and public policy scholarship. It also extends the discourse on religion and governance by demonstrating how local practices in Indonesia can inform global debates on ethical leadership in diverse societies. Practically, this study provides policy insights for governments seeking to design governance structures that respect cultural-religious values while adhering to democratic principles. Overall, the research highlights the potential of Islamic participatory leadership to promote good governance and social cohesio